Stock Characteristics of Humpback Whitefish and Least Cisco in the Chatanika River, Alaska - Sutton, Trent M.; Edenfield, Lorena E. (ARCTIC, 2012)
Overharvest of humpback whitefish (Coregonus pidschian) and least cisco (C. sardinella) in the Chatanika River, Alaska, during the late 1980s led to collapsed stocks and closure of the fishery. We evaluated the stock characteristics of these two species to determine the extent of recovery. A total of 3207 humpback whitefish and 2766 least cisco were captured during their fall spawning migration in 2008. Humpback whitefish ranged from 188 to 583 mm in fork length (FL) and encompassed ages 5 to 29 years, while least cisco ranged from 215 to 425 mm in FL and their ages ranged from 3 to 14 years. Patterns in growth and length-at-age were similar for both species, and annual mortality rates were 31% for humpback whitefish (age 11 and older) and 44% for least cisco (age 9 and older). Population attributes were within the ranges observed for other North American stocks of humpback whitefish and least cisco. Although the humpback whitefish in the Chatanika River have stock attributes that are consistent with low exploitation and this species appears to have recovered, the least cisco in the river still exhibit many attributes that suggest the cisco stock has not fully recovered. The results of this study indicate that the current allowable harvest limit of 2000 whitefish is cautious and appears to be sustainable. Vers la fin des années 1980, la pêche excessive du corégone à bosse (Coregonus pidschian) et de la cisco sardinelle (C. sardinella) dans la rivière Chatanika, en Alaska, a entraîné l’évidement des stocks et la fermeture du lieu de pêche. Nous avons évalué les caractéristiques des stocks de ces deux espèces afin de déterminer l’ampleur de leur rétablissement. Au total, 3 207 corégones à bosse et 2 766 ciscos sardinelles ont été capturés pendant leur frai de migration automnale en 2008. La longueur à la fourche du corégone à bosse variait entre 188 et 583 mm pour des âges allant de 5 à 29 ans, tandis que la longueur à la fourche de la cisco sardinelle variait entre 215 et 425 mm pour des âges allant de 3 à 14 ...